A high temperature resistant high barrier polyethylene film and preparation method thereof
By reasonably proportioning high-density polyethylene, linear low-density polyethylene, and medium-density polyethylene in the polyethylene film, and adding modified montmorillonite to the raw materials, the problem of insufficient barrier properties of traditional polyethylene films is solved, and higher tensile strength, elongation of break and barrier properties are achieved, and it is suitable for medical sterilized respiratory bags.
Patent Information
- Application Number
- CN202411927826.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
The water vapor permeability and oxygen permeability of traditional polyethylene films are high, and the barrier properties are insufficient, making it difficult to meet the high barrier requirements of medical sterilized respiratory bags.
The overall strength and barrier properties of the polyethylene film are improved through reasonable proportioning and preparation methods of modified montmorillonite.
It significantly improves the tensile strength, elongation of break, water vapor permeability and oxygen permeability of the polyethylene film, improves its barrier properties and durability, and is suitable for medical sterilization and respiratory bags and other applications.
Smart Images

Figure BDA0005209634310000091 
Figure BDA0005209634310000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polyethylene films, and more specifically, to a high temperature resistant high barrier polyethylene film and a preparation method thereof. Background Art
[0002] Medical sterilization breathing bags are an indispensable packaging product in the medical field. They are mainly used for the sterilization, storage and transportation of medical devices, biological samples, medicines and other items. Medical sterilization breathing bags need to maintain the stability and sterility of the internal environment during use. Medical sterilization breathing bags mostly use polyethylene film as the packaging material. Polyethylene film is a film produced from polyethylene. It has good low-temperature resistance, chemical stability, acid and alkali corrosion resistance, and electrical insulation. It can keep the medical sterilization breathing bag stable. Traditional polyethylene film often uses linear low-density polyethylene as its raw material, and is combined with antioxidants to obtain polyethylene film. However, the polyethylene film obtained by the above method has a water vapor permeability of as low as 4g / (m 2 24h), oxygen permeability reaches a minimum of 2000cm 3 / (m 2 ·24h·0.1MPa), the barrier property is slightly poor and needs to be further improved. Summary of the invention
[0003] In order to improve the barrier properties of polyethylene films, the present application provides a high temperature resistant high barrier polyethylene film and a preparation method thereof.
[0004] In the first aspect, the present application provides a high temperature resistant high barrier polyethylene film, which adopts the following technical solution: A high-temperature resistant high-barrier polyethylene film is mainly made of the following raw materials in percentage by weight: 35-55% high-density polyethylene, 10-20% linear low-density polyethylene, 30-40% medium-density polyethylene, 1-2% maleic anhydride grafted polyethylene, 2-4% modified montmorillonite, and 1-2% antioxidant; the modified montmorillonite is obtained by treating montmorillonite with 3-aminopropyltrimethoxysilane, carboxymethyl chitosan, stearamide, and glutaraldehyde.
[0005] The high temperature resistant high barrier polyethylene film of the present application has a reasonable ratio of high density polyethylene, linear low density polyethylene and medium density polyethylene, which significantly improves the overall strength and high temperature resistance of the polyethylene film, and can withstand a high temperature of 130°C, showing good high temperature resistance. In addition, modified montmorillonite is added to the raw materials, and through the mutual cooperation between it and other raw materials, the tensile strength of the polyethylene film is greater than 36MPa, the elongation at break is greater than 1200%, and the water vapor permeability is less than 1g / (m 2 ·24h), oxygen permeability <1500cm 3 / (m 2·24h·0.1MPa), showing the characteristics of high tensile strength, high elongation at break, low water vapor permeability, low oxygen permeability, and high barrier properties, which improves the durability and reliability of polyethylene film and is suitable for medical sterilization breathing bags, etc., to meet market demand.
[0006] The high temperature resistant and high barrier polyethylene film of the present application adds modified montmorillonite to the raw materials, and grafts 3-aminopropyltrimethoxysilane, carboxymethyl chitosan, and stearamide on the surface of the montmorillonite, introducing a large number of active groups such as siloxy, hydroxyl, ether, amide, and stearyl groups, and utilizing the interaction between them, which not only increases the dispersibility and binding force of the modified montmorillonite, enhances the interfacial interaction, and improves the integrity, but also blocks the permeation path of water vapor and oxygen, reduces internal voids and defects, reduces the water vapor permeability and oxygen permeability, improves the barrier properties, and makes the polyethylene film exhibit better comprehensive performance.
[0007] Optionally, the modified montmorillonite is mainly prepared by the following method: S1. Mix water and montmorillonite, perform ultrasonic treatment for 5-15 min, add 3-aminopropyltrimethoxysilane, stir for 1-3 h, filter, and obtain silane-grafted montmorillonite; S2. At a temperature of 70-80° C., mix the ethanol aqueous solution and the silane-grafted montmorillonite, add carboxymethyl chitosan and stearamide, add glutaraldehyde, stir for 2-4 hours, filter, wash, and dry to obtain modified montmorillonite.
[0008] Optionally, the weight ratio of montmorillonite, 3-aminopropyltrimethoxysilane, carboxymethyl chitosan and stearamide is (90-110):(14-16):(5-7):(3-5).
[0009] By adopting the above technical scheme, montmorillonite is first dispersed in water, then grafted with 3-aminopropyltrimethoxysilane, and siloxy and amine groups are introduced on the surface, and then carboxymethyl chitosan and stearamide are added, wherein the carboxymethyl chitosan contains amino groups and the stearamide contains amino groups. The amino groups on the surface of the silane-grafted montmorillonite and the amino groups in the carboxymethyl chitosan and the amino groups in the stearamide undergo a cross-linking reaction under the action of glutaraldehyde, and grafting is achieved to obtain modified montmorillonite. The preparation method of the modified montmorillonite of the present application grafts montmorillonite in steps, which is convenient for controlling the grafting reaction, improving the grafting rate, ensuring the stability and quality of the preparation of the modified montmorillonite, and improving the tensile strength and barrier properties of the polyethylene film.
[0010] Optionally, the weight ratio of montmorillonite to glutaraldehyde is (90-110):(0.3-0.5).
[0011] By adopting the above technical solution, the amount of glutaraldehyde added is optimized, the effect of too little glutaraldehyde on the cross-linking reaction is reduced, and the cost increase due to too much glutaraldehyde is also reduced. When the weight ratio of montmorillonite to glutaraldehyde is selected within the range of (90-110): (0.3-0.5), the stability of the grafting reaction of silane-grafted montmorillonite, carboxymethyl chitosan and stearamide can be guaranteed, and the use effect of the modified montmorillonite can be ensured.
[0012] Optionally, the weight ratio of the montmorillonite, water and ethanol aqueous solution is (9-11):(70-130):(70-130), and the mass fraction of ethanol in the ethanol aqueous solution is 40-50%.
[0013] By adopting the above technical solution, the amount of water added in step S1 is optimized, so that the montmorillonite is fully dispersed in the water, the uniformity of the montmorillonite dispersion is ensured, and the agglomeration is reduced. The ethanol aqueous solution in step S2 and the mass fraction of ethanol in the ethanol aqueous solution are also optimized, not only to make the silane-grafted montmorillonite uniformly dispersed in the ethanol aqueous solution, but also to make the silane-grafted montmorillonite, carboxymethyl chitosan, and stearamide fully grafted and reacted, to ensure the stability of the preparation of the modified montmorillonite and the use effect, and to improve the tensile strength and barrier properties of the polyethylene film.
[0014] Optionally, the average particle size of the montmorillonite used in the modified montmorillonite is 1-30 μm. Preferably, the average particle size of the montmorillonite used in the modified montmorillonite is 1-20 μm. More preferably, the average particle size of the montmorillonite used in the modified montmorillonite is 10-20 μm.
[0015] By adopting the above technical solution, the particle size of montmorillonite is optimized, reducing the impact of dispersibility due to too small particle size and the impact of use effect due to too large particle size. When the average particle size of montmorillonite is selected in the range of 1-30 μm, it can significantly reduce the water vapor permeability and oxygen permeability of the polyethylene film, and make it show better barrier properties. In multiple embodiments, the average particle size of montmorillonite used in the modified montmorillonite is 10 μm, and the average particle size can also be set to 1 μm, 5 μm, 15 μm, 20 μm, 25 μm, 30 μm as needed, but it is not limited to the listed values, and other values not listed in this numerical range are also applicable.
[0016] Optionally, the carboxylation degree of the carboxymethyl chitosan is 80-90%. In multiple embodiments, the carboxylation degree of the carboxymethyl chitosan is 85%, and the carboxylation degree can also be set to 80%, 82%, 87%, 90% as required, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] Optionally, the density of the high-density polyethylene is 0.94-0.97 g / cm 3 The density of the linear low-density polyethylene is 0.91-0.93 g / cm 3 The density of the medium density polyethylene is 0.92-0.94 g / cm 3 In various embodiments, the density of the high density polyethylene is 0.95 g / cm 3 , the density of linear low-density polyethylene is 0.92g / cm 3 , the density of medium density polyethylene is 0.93g / cm 3 The density of high-density polyethylene can also be set to 0.94g / cm 3 , 0.96g / cm 3 , 0.97g / cm 3 The density of the linear low-density polyethylene can also be set to 0.91 g / cm 3 、0.93g / cm 3 The density of medium-density polyethylene can also be set to 0.92g / cm 3 、0.94g / cm 3 , but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Optionally, the antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant 264.
[0019] By adopting the above technical scheme, antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant 264 can effectively inhibit the oxidative degradation reaction of the raw materials at high temperature, enhance the antioxidant property and heat resistance stability of the polyethylene film, maintain the stability of the mechanical properties of the polyethylene film, extend the service life of the polyethylene film, and improve the durability and reliability of the polyethylene film.
[0020] Preferably, the antioxidants are two kinds of antioxidants, namely, antioxidant 1010 and antioxidant 168, and the weight ratio of antioxidant 1010 to antioxidant 168 is (1-3):(1-3). In multiple embodiments, the weight ratio of antioxidant 1010 to antioxidant 168 is 2:1, and the weight ratio can also be set to 1:1, 1:2, 1:3, 2:3, 3:1, 3:2 as needed, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0021] Optionally, the polyethylene film has a thickness of 0.01-0.1 mm. Preferably, the polyethylene film has a thickness of 0.02-0.08 mm. More preferably, the polyethylene film has a thickness of 0.02-0.05 mm.
[0022] By adopting the above technical solution, the thickness of the polyethylene film is optimized, so that the polyethylene film maintains good mechanical strength, flexibility and barrier properties, and is also convenient for the processing and use of the polyethylene film to adapt to production lines and market needs. In multiple embodiments, the thickness of the polyethylene film is 0.04 mm, and the thickness can also be set to 0.01 mm, 0.02 mm, 0.03 mm, 0.05 mm, 0.06 mm, 0.07 mm, 0.08 mm, 0.09 mm, 0.1 mm as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] In a second aspect, the present application provides a method for preparing a high temperature resistant high barrier polyethylene film, which adopts the following technical solution: A method for preparing a high temperature resistant high barrier polyethylene film mainly comprises the following steps: The polyethylene film is obtained by mixing high-density polyethylene, linear low-density polyethylene, medium-density polyethylene, maleic anhydride grafted polyethylene, modified montmorillonite and antioxidant, melt-extruding, and blowing film to draw.
[0024] By adopting the above technical solution, the preparation and processing of polyethylene film are facilitated.
[0025] Optionally, in the method for preparing the polyethylene film, the temperature of the melt extrusion is 160-180°C.
[0026] By adopting the above technical solution, the melt extrusion temperature is optimized to ensure that the raw materials have good fluidity, and the raw materials are fully mixed, the uniformity of the mixed materials is enhanced, and the stability and quality of the polyethylene film preparation are ensured. In multiple embodiments, the melt extrusion temperature is 170°C, and the thickness can also be set to 160°C, 163°C, 165°C, 167°C, 173°C, 175°C, 177°C, 180°C as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0027] In summary, this application has at least the following beneficial effects: The high temperature resistant high barrier polyethylene film of the present application is based on high density polyethylene, linear low density polyethylene and medium density polyethylene, and is reasonably proportioned to improve the overall strength and high temperature resistance. Modified montmorillonite is also added to the raw materials, and 3-aminopropyltrimethoxysilane, carboxymethyl chitosan and stearamide are grafted on the surface of the montmorillonite to introduce a large number of active groups, which not only increases the dispersibility and binding force of the modified montmorillonite, enhances the interface interaction and improves the integrity, but also blocks the permeation path of water vapor and oxygen, reduces internal voids and defects, and improves the barrier properties, so that the tensile strength of the polyethylene film is greater than 36MPa, the elongation at break is greater than 1200%, and the water vapor permeability is less than 1g / (m 2 ·24h), oxygen permeability <1500cm 3 / (m 2 ·24h·0.1MPa), showing good high temperature resistance, high tensile strength, high elongation at break, low water vapor permeability, low oxygen permeability, and high barrier properties, improving durability and reliability, and is suitable for medical sterilization breathing bags, etc., to meet market demand. DETAILED DESCRIPTION
[0028] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.
[0029] Preparation Example Preparation Example 1 A modified montmorillonite is mainly prepared by the following method: S1. Add 100 kg of montmorillonite to 1000 kg of water at a stirring rate of 500 rpm, stir for 5 min, and ultrasonically treat for 10 min. Add 15 kg of 3-aminopropyltrimethoxysilane, stir for 2 h, and filter to obtain silane-grafted montmorillonite.
[0030] Among them, the average particle size of montmorillonite is 10 μm, and it is selected from Zhejiang Fenghong New Materials Co., Ltd.
[0031] S2. Add the silane-grafted montmorillonite obtained in step S1 to 1000 kg of 45% ethanol aqueous solution at a stirring rate of 500 rpm and a temperature of 75°C, and stir for 5 minutes. Add 6 kg of carboxymethyl chitosan and 4 kg of stearamide, and stir for 5 minutes. Add 0.4 kg of glutaraldehyde, stir for 3 hours, filter, wash, and dry to obtain modified montmorillonite.
[0032] Among them, the carboxylation degree of carboxymethyl chitosan is 85%, and it is selected from Jinan Xinzhiyuan Biotechnology Co., Ltd.; in the washing treatment, it is washed once with 200 kg of ethanol, washed once with an ethanol aqueous solution with a mass concentration of 80%, washed once with 200 kg of an ethanol aqueous solution with a mass concentration of 50%, and washed once with water to complete the washing treatment.
[0033] Preparation Example 2 A modified montmorillonite is mainly prepared by the following method: S1. Add 90 kg of montmorillonite to 700 kg of water at a stirring rate of 500 rpm, stir for 5 minutes, and ultrasonically treat for 15 minutes. Add 16 kg of 3-aminopropyltrimethoxysilane, stir for 1 hour, and filter to obtain silane-grafted montmorillonite.
[0034] Among them, the average particle size of montmorillonite is 10 μm, and it is selected from Zhejiang Fenghong New Materials Co., Ltd.
[0035] S2. Add the silane-grafted montmorillonite obtained in step S1 to 700 kg of 50% ethanol aqueous solution at a stirring rate of 500 rpm and a temperature of 80° C., and stir for 5 min. Add 5 kg of carboxymethyl chitosan and 5 kg of stearamide, and stir for 5 min. Add 0.5 kg of glutaraldehyde, stir for 4 h, filter, wash, and dry to obtain modified montmorillonite.
[0036] Among them, the carboxylation degree of carboxymethyl chitosan is 85%, and it is selected from Jinan Xinzhiyuan Biotechnology Co., Ltd.; in the washing treatment, it is washed once with 200 kg of ethanol, washed once with an ethanol aqueous solution with a mass concentration of 80%, washed once with 200 kg of an ethanol aqueous solution with a mass concentration of 50%, and washed once with water to complete the washing treatment.
[0037] Preparation Example 3 A modified montmorillonite is mainly prepared by the following method: S1. Add 110 kg of montmorillonite to 1300 kg of water at a stirring rate of 500 rpm, stir for 5 min, perform ultrasonic treatment for 5 min, add 14 kg of 3-aminopropyltrimethoxysilane, stir for 3 h, filter, and obtain silane-grafted montmorillonite.
[0038] Among them, the average particle size of montmorillonite is 10 μm, and it is selected from Zhejiang Fenghong New Materials Co., Ltd.
[0039] S2. Add the silane-grafted montmorillonite obtained in step S1 to 1300 kg of 40% ethanol aqueous solution at a stirring rate of 500 rpm and a temperature of 70°C, and stir for 5 minutes. Add 7 kg of carboxymethyl chitosan and 3 kg of stearamide, and stir for 5 minutes. Add 0.3 kg of glutaraldehyde, stir for 2 hours, filter, wash, and dry to obtain modified montmorillonite.
[0040] Among them, the carboxylation degree of carboxymethyl chitosan is 85%, and it is selected from Jinan Xinzhiyuan Biotechnology Co., Ltd.; in the washing treatment, it is washed once with 200 kg of ethanol, washed once with an ethanol aqueous solution with a mass concentration of 80%, washed once with 200 kg of an ethanol aqueous solution with a mass concentration of 50%, and washed once with water to complete the washing treatment. Example
[0041] Table 1 Raw material dosage of polyethylene film (unit: kg) Example Example 1 Example 2 Example 3 Example 4 Example 5 High Density Polyethylene 44 43 45 35 55 Linear low density polyethylene 15 10 20 20 10 Medium Density Polyethylene 35 40 30 40 30 Maleic anhydride grafted polyethylene 1.5 1 2 2 2 Modified montmorillonite 3 4 2 2 2 Antioxidants 1.5 2 1 1 1 total 100 100 100 100 100 Example 1 A high temperature resistant high barrier polyethylene film, the raw materials and raw material ratios of which are shown in Table 1.
[0042] Among them, the density of high-density polyethylene is 0.95g / cm 3 ; The density of linear low-density polyethylene is 0.92g / cm 3 ; The density of the medium-density polyethylene is 0.93 g / cm3; the maleic anhydride grafted polyethylene is maleic anhydride grafted polyethylene FR-100A, and is selected from Dongguan Xingyuan Chemical Co., Ltd.; the modified montmorillonite is prepared by the method of Preparation Example 1; the antioxidants are antioxidant 1010 and antioxidant 168, and the weight ratio of antioxidant 1010 to antioxidant 168 is 2:1.
[0043] A method for preparing a high temperature resistant high barrier polyethylene film mainly comprises the following steps: At a stirring rate of 300 rpm, linear low-density polyethylene, medium-density polyethylene, maleic anhydride grafted polyethylene, modified montmorillonite, and antioxidant were added to high-density polyethylene and stirred for 30 minutes. Then, at a temperature of 170°C, melt extrusion, film blowing and traction were performed to obtain a polyethylene film with a thickness of 0.04 mm.
[0044] Embodiment 2-5 A high temperature resistant and high barrier polyethylene film, which is different from Example 1 in that the raw material ratio of the polyethylene film is different, and the raw material ratio of the polyethylene film of Examples 2-5 is shown in Table 1.
[0045] Example 6 A high temperature resistant and high barrier polyethylene film, which is different from Example 1 in that the source of the modified montmorillonite in the raw materials of the polyethylene film is different, and the modified montmorillonite is prepared by the method of Preparation Example 2.
[0046] Example 7 A high temperature resistant and high barrier polyethylene film, which is different from Example 1 in that the source of the modified montmorillonite in the raw materials of the polyethylene film is different, and the modified montmorillonite is prepared by the method of Preparation Example 3.
[0047] Comparative Example Comparative Example 1 A high temperature resistant high barrier polyethylene film, which differs from Example 1 in that an equal amount of high density polyethylene is used to replace modified montmorillonite in the raw material of the polyethylene film.
[0048] Comparative Example 2 A high temperature resistant high barrier polyethylene film, which is different from Example 1 in that an equal amount of montmorillonite is used to replace modified montmorillonite in the raw material of the polyethylene film.
[0049] Comparative Example 3 A high temperature resistant and high barrier polyethylene film, which is different from Example 1 in that in the raw material of the polyethylene film, in the preparation method of the modified montmorillonite, steps S1 and S2 are different.
[0050] Step S1 and step S2 are specifically as follows: adding 100 kg of montmorillonite to 1000 kg of water at a stirring rate of 500 rpm, stirring for 5 minutes, ultrasonic treatment for 10 minutes, adding 25 kg of 3-aminopropyltrimethoxysilane, stirring for 5 hours, filtering, washing, and drying to obtain modified montmorillonite.
[0051] Among them, the average particle size of montmorillonite is 10μm, and it is selected from Zhejiang Fenghong New Materials Co., Ltd.; in the washing treatment, it is washed once with 200kg of ethanol, washed once with an ethanol aqueous solution with a mass concentration of 80%, washed once with 200kg of an ethanol aqueous solution with a mass concentration of 50%, and washed once with water to complete the washing treatment.
[0052] Comparative Example 4 A high temperature resistant high barrier polyethylene film, which differs from Example 1 in that, in the raw material of the polyethylene film, in the preparation method of the modified montmorillonite, in step S2, stearamide is replaced by an equal amount of carboxymethyl chitosan.
[0053] Comparative Example 5 A high temperature resistant high barrier polyethylene film, which differs from Example 1 in that, in the raw material of the polyethylene film, in the preparation method of the modified montmorillonite, in step S2, an equal amount of stearamide is used to replace carboxymethyl chitosan.
[0054] Comparative Example 6 A high temperature resistant high barrier polyethylene film, which differs from Example 1 in that an equal amount of modified silicon dioxide is used to replace modified montmorillonite in the raw material of the polyethylene film.
[0055] Modified silica is mainly prepared by the following methods: S1. Add 100 kg of silicon dioxide to 1000 kg of water at a stirring rate of 500 rpm, stir for 5 minutes, and ultrasonically treat for 10 minutes. Add 15 kg of 3-aminopropyltrimethoxysilane, stir for 2 hours, and filter to obtain silane-grafted silicon dioxide.
[0056] Among them, the average particle size of silicon dioxide is 10 μm, and it is selected from Lianyungang Rui Innovation Materials Technology Co., Ltd.
[0057] S2. Add the silane-grafted silica obtained in step S1 to 1000 kg of 45% ethanol aqueous solution at a stirring rate of 500 rpm and a temperature of 75°C, and stir for 5 minutes. Add 6 kg of carboxymethyl chitosan and 4 kg of stearamide, and stir for 5 minutes. Add 0.4 kg of glutaraldehyde, stir for 3 hours, filter, wash, and dry to obtain modified silica.
[0058] Among them, the carboxylation degree of carboxymethyl chitosan is 85%, and it is selected from Jinan Xinzhiyuan Biotechnology Co., Ltd.; in the washing treatment, it is washed once with 200 kg of ethanol, washed once with an ethanol aqueous solution with a mass concentration of 80%, washed once with 200 kg of an ethanol aqueous solution with a mass concentration of 50%, and washed once with water to complete the washing treatment.
[0059] Comparative Example 7 A high temperature resistant high barrier polyethylene film, which differs from Example 1 in that an equal amount of modified alumina is used to replace modified montmorillonite in the raw material of the polyethylene film.
[0060] Modified alumina is mainly prepared by the following methods: S1. Add 100 kg of alumina to 1000 kg of water at a stirring rate of 500 rpm, stir for 5 min, and ultrasonically treat for 10 min. Add 15 kg of 3-aminopropyltrimethoxysilane, stir for 2 h, and filter to obtain silane-grafted alumina.
[0061] Among them, the average particle size of alumina is 10μm and is selected from Lianyungang Rui Innovation Materials Technology Co., Ltd.
[0062] S2. Add the silane-grafted alumina obtained in step S1 to 1000 kg of 45% ethanol aqueous solution at a stirring rate of 500 rpm and a temperature of 75°C, and stir for 5 minutes. Add 6 kg of carboxymethyl chitosan and 4 kg of stearamide, and stir for 5 minutes. Add 0.4 kg of glutaraldehyde, stir for 3 hours, filter, wash, and dry to obtain modified alumina.
[0063] Among them, the carboxylation degree of carboxymethyl chitosan is 85%, and it is selected from Jinan Xinzhiyuan Biotechnology Co., Ltd.; in the washing treatment, it is washed once with 200 kg of ethanol, washed once with an ethanol aqueous solution with a mass concentration of 80%, washed once with 200 kg of an ethanol aqueous solution with a mass concentration of 50%, and washed once with water to complete the washing treatment.
[0064] Performance Testing (1) The polyethylene films obtained in Examples 1-7 were respectively taken and tested according to GB / T16886, YBB00132002, and the Chinese Pharmacopoeia (2015 edition). According to the test, the polyethylene films of Examples 1-7 had skin sensitization ≤ Grade I, no heavy metal dissolution was detected, no oxidizable substance dissolution was detected, no Escherichia coli was detected, no Staphylococcus aureus was detected, and no Pseudomonas aeruginosa was detected, and had good safety.
[0065] (2) The polyethylene films obtained in Examples 1-7 and Comparative Examples 1-7 were respectively taken and the following performance tests were performed on the polyethylene films. The test results are shown in Table 2.
[0066] Among them, according to YBB00112003-2015 "Determination of Tensile Properties", the tensile strength and elongation at break of the polyethylene film were tested, and the standard requirements for medical sterilization breathing bags require that the tensile strength should not be less than 10MPa and the elongation at break should not be less than 200%.
[0067] According to YBB00092003-2015 "Water Vapor Permeability Test Method", the water vapor permeability of polyethylene film is tested, and the standard for medical sterilization breathing bags requires that the water vapor permeability should not exceed 15g / (m 2 ·24h).
[0068] According to YBB00082003-2015 "Gas Permeation Measurement Method", the oxygen permeation of polyethylene film is tested, and the standard for medical sterilization breathing bags requires that the oxygen permeation should not exceed 4000cm 3 / (m 2 ·24h·0.1MPa).
[0069] Table 2 Test results As can be seen from Table 2, the polyethylene film of the present application has higher tensile strength and elongation at break, with a tensile strength of 36.44-39.56 MPa and an elongation at break of 1236-1336%, showing the advantages of high tensile strength and high elongation at break. It also has lower water vapor permeability and oxygen permeability, with a water vapor permeability of 0.56-0.93 g / (m 2 ·24h), oxygen permeability is 1045-1405cm 3 / (m 2 ·24h·0.1MPa), showing high barrier properties, suitable for medical sterilization breathing bags, meeting market demand.
[0070] Comparative Examples 1-2 are compared. No montmorillonite is added to the raw materials of the polyethylene film of Comparative Example 1; montmorillonite is added to the raw materials of the polyethylene film of Comparative Example 2. It can be seen that adding montmorillonite to the raw materials of the polyethylene film can improve the tensile strength and barrier properties. Combined with Comparative Example 3, modified montmorillonite is added to the raw materials of the polyethylene film of Comparative Example 3, and the montmorillonite is treated with 3-aminopropyltrimethoxysilane. It can be seen that modifying montmorillonite and grafting organic matter on the surface can further improve the tensile strength and barrier properties, and make the modified montmorillonite show better use effect.
[0071] Comparative Examples 3-5 and Example 1 are compared. The modified montmorillonite of Comparative Example 3 is obtained by treating montmorillonite with 3-aminopropyltrimethoxysilane; the modified montmorillonite of Comparative Example 4 is obtained by treating montmorillonite with 3-aminopropyltrimethoxysilane and carboxymethyl chitosan; the modified montmorillonite of Comparative Example 5 is obtained by treating montmorillonite with 3-aminopropyltrimethoxysilane and stearamide; the modified montmorillonite of Example 1 is obtained by treating montmorillonite with 3-aminopropyltrimethoxysilane, carboxymethyl chitosan and stearamide. It can be seen from this that 3-aminopropyltrimethoxysilane is grafted on the surface of montmorillonite, siloxy groups and amine groups are introduced, and glutaraldehyde is further used to realize the grafting of carboxymethyl chitosan and stearamide, and active groups such as hydroxyl groups, ether groups, amide groups, and stearyl groups are introduced. By utilizing the synergistic enhancement between them, the dispersibility and interfacial bonding strength of the modified montmorillonite can be enhanced, the overall structure can be improved, and the tensile strength, elongation at break, and barrier properties can be improved.
[0072] Comparative Examples 6-7 and Example 1 are compared. Modified silica is added to the raw material of the polyethylene film of Comparative Example 6; modified alumina is added to the raw material of the polyethylene film of Comparative Example 7; and modified montmorillonite is added to the raw material of the polyethylene film of Example 1. It can be seen that, compared with adding modified silica or modified alumina to the raw material of the polyethylene film, adding modified montmorillonite to the raw material can further improve the tensile strength and elongation at break of the polyethylene film, and reduce the water vapor permeability and oxygen permeability of the polyethylene film, so that the polyethylene film exhibits better comprehensive performance.
[0073] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.
Claims
1. A high temperature resistant high barrier polyethylene film, characterized in that: The polyethylene film is mainly made of the following raw materials in percentage by weight: 35-55% high-density polyethylene, 10-20% linear low-density polyethylene, 30-40% medium-density polyethylene, 1-2% maleic anhydride grafted polyethylene, 2-4% modified montmorillonite, and 1-2% antioxidant; the modified montmorillonite is obtained by treating montmorillonite with 3-aminopropyltrimethoxysilane, carboxymethyl chitosan, stearamide, and glutaraldehyde.
2. The high temperature resistant high barrier polyethylene film according to claim 1, characterized in that: The modified montmorillonite is mainly prepared by the following method: S1. Mix water and montmorillonite, perform ultrasonic treatment for 5-15 min, add 3-aminopropyltrimethoxysilane, stir for 1-3 h, filter, and obtain silane-grafted montmorillonite; S2. At a temperature of 70-80° C., mix the ethanol aqueous solution and the silane-grafted montmorillonite, add carboxymethyl chitosan and stearamide, add glutaraldehyde, stir for 2-4 hours, filter, wash, and dry to obtain modified montmorillonite.
3. The high temperature resistant high barrier polyethylene film according to claim 2, characterized in that: The weight ratio of the montmorillonite, 3-aminopropyltrimethoxysilane, carboxymethyl chitosan and stearamide is (90-110):(14-16):(5-7):(3-5).
4. The high temperature resistant high barrier polyethylene film according to claim 2, characterized in that: The weight ratio of the montmorillonite to glutaraldehyde is (90-110):(0.3-0.5).
5. The high temperature resistant high barrier polyethylene film according to claim 2, characterized in that: The weight ratio of the montmorillonite, water and ethanol aqueous solution is (9-11):(70-130):(70-130), and the mass fraction of ethanol in the ethanol aqueous solution is 40-50%.
6. The high temperature resistant high barrier polyethylene film according to claim 1, characterized in that: The average particle size of the montmorillonite used in the modified montmorillonite is 1-30 μm.
7. The high temperature resistant high barrier polyethylene film according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant 264.
8. The high temperature resistant high barrier polyethylene film according to claim 1, characterized in that: The thickness of the polyethylene film is 0.01-0.1 mm.
9. A method for preparing a high temperature resistant high barrier polyethylene film according to any one of claims 1 to 8, characterized in that: The main steps are as follows: The polyethylene film is obtained by mixing high-density polyethylene, linear low-density polyethylene, medium-density polyethylene, maleic anhydride grafted polyethylene, modified montmorillonite and antioxidant, melt-extruding, and blowing film to draw.
10. The method for preparing a high temperature resistant high barrier polyethylene film according to claim 8, characterized in that: In the method for preparing the polyethylene film, the temperature of the melt extrusion is 160-180°C.